Common sources, perceived communication efficacy and sufficiency of cervical cancer information, education and communication materials for women with HIV/AIDS in rural Kenya - Adeli, Scholastic Musakali; Orang'O, Elkanah Omenge; Naanyu, Violet; Mwangi, Ann; Itsura, Peter; Rosen, Barry; Loehrer, Patrick (Frontiers in Cancer Control and Society, 2025)
IntroductionCervical cancer is the greatest cause of cancer-related death among women in Sub-Saharan Africa, with particularly high incidence and mortality rates in rural regions. In Kenya, Women with HIV/AIDS (WLHA) are at a greater risk of developing cervical cancer though screening rate remains low. Information, education and communication (IEC) materials play a crucial role in raising awareness, promoting screening, and supporting early detection and treatment; however, little is known about the accessibility, content, and perceived effectiveness of these materials from the perspective of WLHA.MethodsThe objective of this study was to determine the common sources, perceived communication efficacy and sufficiency of IEC materials among WLHA and attending clinics in Webuye and Mosoriot both which are health facilities in rural Kenya. Data were collected using a researcher administered questionnaire for 380 WLHA and an IEC checklist for 20 Key stakeholders resulting in a total sample size of 400 participants.ResultsSixteen sources of information were identified, with the most common and preferred being radio, health professionals, support groups, chief's mabaraza and posters. Indicators for communicative efficacy revealed that cervical cancer IEC print materials were not effective in format (77%), the location where they are placed (60%), and graphical appeal (50%). Additionally, 66% of participants found the IEC materials insufficient, inaccessible, and inappropriate.DiscussionWhile a variety of cervical cancer IEC materials exist, WLHA in rural Kenya perceive significant gaps in the availability and effectiveness of these materials. Some IEC materials are preferred because they offer direct interaction, cultural relevance, and broader outreach.